Activity modulated low platium content oxygen reduction electrocatalysts prepared by inducing nano-order dislocations on carbon nanofiber through N-2-doping - Palaniselvam, Thangavelu; Irshad, Ahamed; Unni, Bipinlal; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2012)
We demonstrate how surface unsaturation developed during small order buckling of graphene interlayer upon doping iron nitride (i.e., FeNx) moieties in carbon nanofiber can be utilized as a very efficient mode of surface activation to establish fine distribution of Pt nanoparticles with 10 wt %. The surface dislocations have been effectively modulating the oxygen reduction characteristics of Pt through synergistic effects of the interacting species. The simultaneous enhancement of dispersion of Pt and oxygen reduction reaction (ORR) activity with a low weight percentage of dispersed Pt has been attained by FeNx doping, which increases the density of the active sites owing to the formation of fine and abundant delaminated regions on the CNF surface. HR-TEM images clearly depict the fine distribution of Pt nanoparticles on the delaminated regions of FeNxCNF. The stable incorporation of Pt on nitrogen doped active sites has been further confirmed by observing the formation of Pt-N peak at 391.5 eV using XPS analysis. The fine distribution of Pt nanoparticles along the abundant nanopockets between the buckled graphene layers helped the system to attain significantly high electrochemically active surface area of Pt as evident from the cyclic voltammetric studies. The mass activity of PtFeNxCNF at 0.9 V vs RHE is 4.9 mA mgPt(-1) which is two times higher than that of E-TEK. The superior catalytic activity (exchange current density (i(0)) at 0.8 V is 2.61X 10(-6)) could be further confirmed by single cell evaluation of the membrane electrode assembly (MEA) of polymer electrolyte fuel cell (PEFC), where the cathode electrode was fabricated from this new catalyst.

Effect of the viscosity of poly(benzimidazole) on the performance of a multifunctional electrocatalyst with an ideal interfacial structure - Balan, Beena K.; Unni, Bipinlal; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2013)
A novel electrocatalyst system with unique multifunctional characteristics, originated by the presence of a proton conducting polybenzimidazole (PBI-BuI) bound layer and electron conducting hollow carbon nanofibers (CNF) with catalytically active Pt nanoparticles, has been devised based on a simple strategy. This was achieved by decorating Pt nanoparticles along the inner cavity, as well as on the outer walls of the hollow CNF support (F-Pt). In a further extension, a low molecular weight PBI, synthesized by optimizing the experimental parameters, was incorporated into the inner cavity and along the outer surfaces of F-Pt. Excellent dispersion of the Pt nanoparticles was achieved by properly utilizing the available carbon surface results in improved electrocatalytic activity, while the CNF backbone ensures high electron conductivity as well. The polymer binder coverage formed along the inner and outer wall surfaces provides an efficient triple phase boundary (TPB) around the Pt nanoparticles to facilitate the electrode reactions. The amount and the viscosity of the PBI-BuI in the electrode material were systematically varied to study the influence on the electrochemical performance. Transmission electron microscopy analysis confirms PBI insertion into the tubular cavity of CNF. Pore size distribution analysis implies that both the viscosity and the amount of PBI-BuI have a pivotal role in defining the microstructure of the electrode. Electrochemical studies using cyclic voltammetry (CV) and rotating disc electrode (RDE) reveal the exceptionally high activity of this hybrid material with an improved electrochemically active area. The significant improvement for the oxygen reduction reaction is further confirmed by the single cell analysis also. The high power density displayed by the PBI-BuI based system, as compared to the Nafion based system, validates the conceptualization of the well controlled triple-phase boundary in the system. These results demonstrate that PBI-BuI has a constructive effect in tuning the electrochemical activity at an optimum amount and at a favourable viscosity of the proton conducting polymer.